Effect of head wear and lateral forces on underhead radius crack propagation. (August 2014) - Ranjha, Sagheer Abbas; Mutton, Peter; Kapoor, Ajay
This paper investigated the effect of rail head wear (HW) and lateral forces on underhead radius stress conditions and resulting stress intensity factors (SIFs) of a long transverse crack. The occurrence of tension spikes at the underhead radius of the rail as a result of localised vertical and lateral bending of the head-on-web was significantly exacerbated with increasing rail HW. The extended finite element method (X-FEM) modelling, which had previously been validated by comparison with in-track measurements to verify the prediction of tension spikes, was used to model a single rail on discrete elastic foundations. SIFs along the crack front were parametrically evaluated in terms of changes in the contact patch offset (CPO), the ( L / V ) ratio of lateral ( L ) to vertical ( V ) loads, the rail HW, and crack size and shape. The X-FEM results revealed that for a long transverse crack, extending the crack length to the underhead radius position results in higher SIFs across the underhead radius as a result of tensile bending stresses. These higher SIFs can contribute to a massively higher crack growth rate at this location, as was evidenced by the crack growth morphology at the underhead radius.